Seroprevalence and Risk Factors of Syphilis among Blood Donors - Singhal, Sachin; Sharma, Dharmesh Chandra; Rai, Sunita; Arya, Anita; Gupta, Prakriti (Journal of College of Medical Sciences-Nepal, 2021)
Abstract Background: Transfusion of blood /component is an essential procedure in modern days of medical practice. As far as safe transfusion is concerned, it is a prime requirement i.e. handles TTIs infections including syphilis and other adverse events. Aims and Objectives: Focus of the present study is to assess seroprevalence and risk factors of Syphilis among blood donors in greater Gwalior Materials and Methods: The present retrospective descriptive study was conducted over a period of 8 years. All the samples of voluntary and relative blood donors, who came to donate blood, were tested for transfusion transmissible infections. Prevalence of TTIs and syphilis were analyzed in the view of different parameters of donors and along with its associated risk factors. Chi square (X2) test was applied to know the significant (p value) ratio of difference statistically as required. Results: In the present study prevalence of TTIs is 3.44% and for syphilis it is 0.268%, most common age group is 40-51years (41.18%); male to female ratio is insignificant statistically. Ratio of voluntary versus relative donors was 94.21% and 5.79 % and male to female was 91.27% and 8.473% were female respectively. Conclusion: An advance knowledge, attitude, and behavior of the volunteer blood donors’ population regarding risk factors will most probably improve public health and increase blood safety and quality.